PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP PERILAKU KEKERASAN PADA PASIEN JIWA DI PUSKESMAS REJOSO KABUPATEN NGANJUK - Wahyudi, Heru; Ambarwati, Rustiati Oktafaruna; Suwandi, Cucuk (JURNAL SABHANGA, 2021)
Efforts to overcome mental patient with the risk of violent behavior generally still use binding or restrain, but this raises the ethical of mental nursing profession, so nursing care needed in the form of therapeutic communication. The purpose of this study was to determine the effect of therapeutic communication on changes in violent behavior in mental patients at the Rejoso Health Center in Nganjuk Regency. This is evidence from the results of testing the research hypothesis by using paired sample T-Test resulting in p-value=0.000.